ANALISIS PERMINTAAN KEDELAI DI KABUPATEN BANYUMAS JAWA TENGAH - SAHARA, DEWI; GUNAWATI, ENDANG S. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005, 2012)
Soybean demand analysis research in Banyumas regency used time series data from 1994 – 2003. Soybean demand function was estimated by double dynamic linear regression analysis model in logarithm with put last year demand variable. Analysis result showed the factor affected soybean demand were price of soybean, population, and price of corn. Decreasing of soybean demand was caused by decreasing of soybean price and corn price. The demand will increase together with increase in population. Soybean demand was elastic to both price change and income change. This meant that increasing of income may cause increasing of soybean quantity on each increasing of price, so soybean was normal goods. Elasticity crossed obtained was smaller than one (EQ,P1 < 1), so it was complement relationship between corn and soybean. Short run soybean demand elasticity value was larger than long run demand. It meant that in short run, demand change was directly influenced by change of price and income, but in long run context, its change response tends to decrease due to adaptation process.
Keywords: Soybean Demand, Elasticity, Price, Income